2018
DOI: 10.1038/s41598-018-26191-0
|View full text |Cite
|
Sign up to set email alerts
|

High Redundancy as well as Complementary Prey Choice Characterize Generalist Predator Food Webs in Agroecosystems

Abstract: Food web structure influences ecosystem functioning and the strength and stability of associated ecosystem services. With their broad diet, generalist predators represent key nodes in the structure of many food webs and they contribute substantially to ecosystem services such as biological pest control. However, until recently it has been difficult to empirically assess food web structure with generalist predators. We utilized DNA-based molecular gut-content analyses to assess the prey use of a set of generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 47 publications
1
55
1
Order By: Relevance
“…Spontaneously high detections of aphids as food in individual fields would tend to support their potential as aphid biocontrol agents (Harwood and Obrycki 2005 ). Overall detection rates of lumbricid and collembolan alternative prey were higher than in Staudacher et al ( 2016 ) and lower than in Roubinet et al ( 2017 , 2018 ). However, in concurrence with our results, these studies revealed a preference for lumbricids over collembolans in P. cupreus and P. melanarius and the reverse preference in P. rufipes .…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Spontaneously high detections of aphids as food in individual fields would tend to support their potential as aphid biocontrol agents (Harwood and Obrycki 2005 ). Overall detection rates of lumbricid and collembolan alternative prey were higher than in Staudacher et al ( 2016 ) and lower than in Roubinet et al ( 2017 , 2018 ). However, in concurrence with our results, these studies revealed a preference for lumbricids over collembolans in P. cupreus and P. melanarius and the reverse preference in P. rufipes .…”
Section: Discussioncontrasting
confidence: 67%
“…dipterans, thrips and intraguild prey, such as other carabid species or spiders. Low levels of predation on aphids, in comparison with other studies in European cereal fields (Staudacher et al 2016 ; Roubinet et al 2017 , 2018 ), may be ascribed to the fact that there were only few aphids present in the sampled fields. Spontaneously high detections of aphids as food in individual fields would tend to support their potential as aphid biocontrol agents (Harwood and Obrycki 2005 ).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…For example, seasonal changes in species composition cause temporal variation in the strength of interactions (Carnicer et al, ; Gabaldón et al, ; Wang et al, ), as well as changes in food web topology and structure (McLaughlin, Jonsson, & Emmerson, ). In agroecosystems, temporal variability in species interaction strength is detectable even within crop seasons, as recently shown by Roubinet et al () in a barley field. Therefore, because a species’ fundamental trophic niche (all of its potential interactions) is unlikely to be realized at a particular place or time, it is crucial to determine the resources which species in a community actually feed upon, and under what circumstances.…”
Section: Discussionsupporting
confidence: 61%
“…Generalism appears to be the norm in typical food webs, while specialism tends to be more common in mutualistic interaction networks (Ings et al, ). For instance, food webs of invertebrate predators in temperate agricultural fields were dominated by generalists ( H 2 ˈ : 0.22; Roubinet et al, ; see also van Veen, Müller, Pell, & Godfray, ). Compared to typical food webs, the army ant–prey network showed an exceptionally high degree of interaction specificity ( H 2 ˈ = 0.66).…”
Section: Discussionmentioning
confidence: 99%